The pozzolanic reaction of mechanically treated coal bottom ash in a cementitious environment of self-compacting concrete - Mohammad Ismail Yousef, Albiajawi (2024)
The use of industrial waste such as coal bottom ash (CBA) in the production of concrete is an ecological alternative would be able to minimize the amount of main resources consumed in the construction industry and reduce CBA waste disposal. Due to the economic and environmental benefits of CBA, the attention of researchers has taken to use of industrial waste to introduce new building materials such as CBA in selfcompacting concrete (SCC). Most of the literature discussed the utilization of CBA as fine aggregate in concrete but using ground CBA as cement replacement in SCC has not been investigated yet. Furthermore, this study is to use ground CBA with various replacements ratios for cement in the production of SCC. Unique characteristic of CBA as one of the industrial by-products that has high pozzolanic properties, which is highly recommended to be used as partial cement replacement in SCC. Therefore, this study aims to investigate the effect of ground CBA as partial cement replacement on the properties of SCC. The ground CBA was used as partial replacement of cement from 10% to 50%. While other SCC materials (water, coarse aggregate, fine aggregate, and super-plasticizer content) were kept constant in all SCC mixes. First, this study aims to evaluate the physical, chemical, and microstructural properties of mechanically treated CBA as pozzolanic materials to determine its suitability for use in the production of SCC. Thereafter, the influence of pozzolanic properties of different sizes by various grinding cycles (3000, 5000, 7000 cycles) of ground CBA is investigated by thermogravimetric analysis (TGA), strength activity index (SAI), Chapelle test and Frattini test. After that, the optimum grinding size with better performance has been used to prepare the SCC mixture. Furthermore, the ground CBA was tested in the fresh properties of SCC containing CBA such as Flow slump, L-Box, V-funnel, J-Ring, and compared to SCC without ground CBA in the mixture. Then, the influence of SCC containing ground CBA on the mechanical properties such as the compressive strength, ultrasonic pulse velocity (UPV), flexural strength and tensile strength were conducted after 7, 14, 28, 56, 90, and 180 days of curing compared to SCC without ground CBA in the mixture. Other than that, the durability properties of SCC such as water absorption, acid resistance, and sulphate resistance were conducted to determine the durability of SCC. Apart from that, the effect of SCC containing ground CBA subjected to various elevated temperature test was conducted. The findings of this study were found up to CBA 20% the optimum as cement replacement that observed significant improvements in fresh and mechanical properties of SCC compared to those of control SCC at later curing ages after 28 days. However, the inclusion of ground CBA improves the characteristics of the SCC specimens due to the pozzolanic impact of the siliceous nature of ground CBA, particularly during the later curing ages after 28 days. On the other hand, For the durability properties incorporation ground CBA exhibiting to higher water absorption due to high porous and void compared to SCC control samples. In terms of acid the SCC specimens containing ground CBA experience more deterioration as compared to control SCC after immersed in sulfuric acid solution. In terms of sulphate resistance showed that ground CBA10% of SCC exhibited better durability when exposed to sulphate solution. SCC containing ground CBA10% also exhibits better resistance upon subjected to elevated temperature. From this study, achieving success in the production of ecofriendly SCC with ground CBA could lead to a more pristine environment and promote sustainable building practices.